Analysis of the Impact of Communication and Job Satisfaction on Work Effectiveness at the Department of Cooperatives, Small and Medium Enterprises, Industry and Trade (DKUKMPP), Solok Regency - Nasrah, Rasidah; Mursalini, Wahyu Indah; Sutriani, Rahmi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
This study aims to investigate how communication and job satisfaction impact work effectiveness at the Solok Regency Small and Medium Enterprises Cooperatives, Industry and Trade (DKUKMPP) Service. A total of 67 respondents participated in the research, which utilised quantitative methods for analysis. The statistical analysis revealed that communication has a significant influence on work effectiveness, as evidenced by the t test results (tvalue 4.536 > ttable 1.998, significance level 0.000 < 0.05). This suggests that effective communication plays a crucial role in enhancing work effectiveness. Furthermore, the study concluded that job satisfaction also has a significant impact on work effectiveness, based on the statistical analysis findings.  The t-test confirmed that the value of tvalue 4.018 is greater than ttable 1.998, indicating that Job Satisfaction has a significant impact on Work Effectiveness. Furthermore, it was found that both Communication and Job Satisfaction together have a significant effect on Work Effectiveness within the Solok Regency Small and Medium Enterprises Cooperatives, Industry and Trade (DKUKMPP) Service. This was demonstrated through the use of the F test, where the fvalue of 76.332 exceeded the ftable value of 3.14, with a resulting significance value of 0.000, which is lower than the threshold of 0.05. The R Square value of 0.705, representing 70.5%, suggests that Job Satisfaction and Communication explain a significant portion of Work Effectiveness, with 29.5% of the influence coming from other variables not accounted for in the study.